SENTIDO E SATISFAÇÃO NO TRABALHO: UM ESTUDO ENTRE GESTORES EDUCACIONAIS - Pinto, Vera Regina Ramos (2010)
This research presents and analyzes the perception on the meaning of work and job satisfaction, from a group of educational managers. Based on the main theoretical constructs in the researched field, a data collection instrument was assembled, with assertions on these subjects. A non-probability sample was selected, composed of 105 school managers from SESI/SENAI education system, coming from different states of the country, and 46 educational managers from public schools of Rio de Janeiro State, all of them participants of the first MBA course in Enterpreneuring Management, offered by Universidade Federal Fluminense. As a member of the research group from the Management and Entrepreneurship Graduate Program, responsible for this MBA, the author was motivated to study the subject in view of the limited academic research focused on educational managers.A descriptive analysis of the data concluded, among others findings, that work is one of the most important elements in the life of the school manager, but not the most important one. For these groups the main function of work is serving the society. Both groups had chosen the opportunity to learn new things as the most important element that a work must offer, and they are very satisfied in this aspect. Good physical conditions and interpersonal relationships at work also had been detached as important, but they present a lesser level of satisfaction. Respondents said to be very satisfied with their organizations, therefore they have pride in saying where they work and they believe that those organizations contribute for the social development of the communities where they are inserted. For the educational managers from public schools, the greatest levels of satisfaction are related to the pleasure that working provides and to the accomplishment gotten with the work, while, for the respondents of SESI/SENAI, the possibility of personal growth and professional growth they had presented the greatest level of satisfaction. Factor analysis was used as a way to reduce the amount of variable and to facilitate the finding of correlations between meaning of work and job satisfaction. This analysis allowed to identify six new variates, two of them related to the meaning of work, namely: centrality of work and the paper of work. The four other variates are related to job satisfaction: recognition, accomplishment, remuneration and physical conditions at work. Correlations of stronger intensity were found among the variates related to job satisfaction, and weak correlation between meaning of work and job satisfaction.